Patient‐derived xenografts of a case of ameloblastic fibrodentinoma. (27th February 2019) - Pereira, Núbia B.; de Souza, Juliana C.; Bastos, Victor C.; Fonseca, Felipe P.; de Avelar, Gleide F.; Castro, Wagner H.; Dias, Adriana A. M.; Mosqueda‐Taylor, Adalberto; Gomez, Ricardo S.; Gomes, Carolina C.
Abstract: Objectives: The establishment of animal models of xenotransplantation can contribute to the elucidation of the molecular pathogenesis of ameloblastic fibrodentinomas (AFD) and it also provides an opportunity for drug tests. We aimed to evaluate the possibility of AFD tumour growth in a patient‐derived xenograft (PDX) model. In addition, we characterized the human tumour and the PDXs. Materials and Methods: A sample of a recurrent AFD was obtained and two fragments were contralaterally implanted subcutaneously in an 8‐week old female NUDE mouse. After 250 days, the PDXs were removed and submitted to histopathological and molecular analysis. Immunohistochemical reactions for Ki67 and the phosphorylated form of ERK1/2 were carried out in both, PDXs and human tumour, and the presence of BRAFV600E was assessed. Results: From day 135 onwards, the PDXs presented a growth peak and remained stable until day 250. Histopathologically, the PDXs presented the same features of the patient's tumour. Tumour cells exhibited Ki67 and pERK1/2 immunoexpression in the patient's tumour and PDX. The AFD was wild‐type for BRAFV600E. Conclusion: The PDX model recapitulated well the human tumour after a long implantation time, representing a possible model to study the AFD and other odontogenic tumours pathobiology.